Influence of Hesperetin Concentration in Poloxamer P84 and TPGS Mixed Micelles on Physical Characteristics and Cytotoxicity in T47D Cell Line - Aulia, Nanda Intan; Rijal, Muh. Agus Syamsur; Yusuf, Helmy (Universitas Airlangga, 2025)
Background: Hesperetin is a natural compound that has several properties including anticancer, but has limitation on low solubility in water. In this case, the development of a hesperetin delivery system using the micellar system is carried out. Objective: The current study aims to determine the effect of drug concentration on the physical characteristics and cytotoxicity of the mixed micelle. Methods: In this study, mixed micelles were formulated with D-a-tocopheryl polyethylene glycol 1000 succinate (TPGS) and poloxamer P84 as polymers through the thin film method, with hesperetin loaded at four different concentrations, i.e., 5 mg (F1), 10 mg (F2), 20 mg (F3), and 40 mg (F4). The mixed micelles were formulated using thin film hydration method. The evaluation of micelle’s physical characteristics was the measurement of particle size, Critical Micelle Concentration (CMC) value, drug loading, and drug entrapment efficiency. The evaluation of cytotoxicity used the T47D cell line and Micro Tetrazolium (MTT) method. Results: The CMC value of the mixed micelle was 0.0029% w/v, which was lower than the CMC of TPGS and poloxamer P84 only. The particle size of the micelles produced was between 17.07–20.37 nm. Among the various formulations, F3 showed relatively small particle size and has homogeneous particle size, high drug loading and encapsulation efficiency, and low IC50. Based on the study, particle size of F3 was 17.93 0.32 nm with polydispersity index (PDI) of 0.256 0.034. The drug loading percentage of F3 was 4.0092 0.0048% with an encapsulation efficiency of 94.5492 0.0013%. Based on cytotoxicity test using MTT method, F3 has low IC50, there was 4.036 ppm. Conclusion: Hesperetin-loaded mixed micelles offer potential as anticancer drugs that improve hesperetin efficacy. The results showed that F3 was the most potent anticancer formulation based on the physical characteristics and cytotoxicity tests.